PENERAPAN PASAN 32 AYAT(2) PERATURAN PEMERINTAH NOMOR 24 TAHUN 1997 TENTANG PENDAFTARAN TANAH OLEH PENGADILAN - Leks, Eddy Marek; Fitri Nabilla Aulia (Jurnal Paradigma Hukum Pembangunan, 2023)
Land is an important asset to every person. Therefore, clarity on land ownership and protection towards land owner is also important. To achieve that, the Government has issued Government Regulation on Land Registration. The final result from the land registration is the issuance of proof of right, in the form of land certificate that constitutes as strong evidence as regulated in Article 19 paragraph (2) of UUPA. This means that land certificate is not the only evidence or absolute evidence. Accordingly, the certificate holder still faces the risk of cancellation or claim on land ownership from other parties. Article 32 paragraph (2) of Government Regulation on Land Registration was intended to mitigate the legal risks of land ownership disputes. This research has the objective to observe the extent to which Article 32 paragraph (2) of Government Regulation on Land Registration and its elements are implemented in court. Based on the normative legal research method with case study approach in court from 2009 to 2021, we found that out of 100% (355 decisions) we examined mentioning the Article 32 paragraph (2) of Government Regulation on Land Registration, in the majority of decision, namely 84% (299 decisions), the panel of judges did not refer to that clause in their legal consideration, whereas the remaining 16% (56 decisions), the panel of judges directly referred that clause. From the 16% of the disputes, 95% (53 decisions) fully applied Article 32 paragraph (2) Government Regulation on Land Registration and the remaining 5% (3 decisions) was considered as non-contextual due to being related to customary land. Based on our research, in courts applying Article 32 paragraph (2) of Government Regulation on Land Registration, the elements regarding the issuance of the valid certificate and land certificate has passed 5 (five) years are the two most considered elements by the courts.